"Not even blood mixture could make them unworthy": political loyalty and tribute in Bourbon New Spain. Issue 2 (4th May 2018) - Gharala, Norah L. A.
ABSTRACT: This article examines the shifting meanings of calidad and political loyalty as they applied to tributary status in Bourbon New Spain. While tribute had long remained a symbol of the relationship between crown and subject, Bourbon bureaucrats began to employ the language of calidad to explain tributary obligations. The use of calidad led to the creation of a robust tributary population that by mid-century produced record amounts of revenue. Despite the late-colonial expansion of tribute, bureaucrats would never reach a consensus regarding the precise nature of tributary status or calidad . I examine claims to conquistador ancestry from the early-eighteenth century to explore the uses of genealogy, calidad, and physical appearance as determinants of tributary status. Comparing an early case study with bureaucratic opinions from the end of the century, I argue that petitions for tribute exemption provided a forum for ordinary people and bureaucrats to debate the meanings of political loyalty and family history. Bureaucrats attempted to limit the extent to which the privileges granted to descendants of conquistadors could coexist with Afromexican calidad, while Afromexicans used petitions to establish a lineage of loyalty and services which could exempt them from tribute.